The almighty chance - Zeldovich, Ya B.; Ruzmaikin, A. A.; Sokoloff, D. D (Singapore World Scientific Publishing, 1990)
This book takes a new look at the problem of structure formation in random media, qualitative physical representation of modern conceptions, intermittency, fractals, percolation and many examples from different fields of science.
Includes references and index
Keywords: Cơ bản